Overcoming Selfishness: Reciprocity, Inhibition, and Cardiac-Autonomic Control in the Ultimatum Game - Sütterlin, Stefan; Herbert, Cornelia; Schmitt, Michael; Kübler, Andrea; Vögele, Claus (Frontiers in Psychology, 2011)
The processes underlying decision-making in response to unfair offers in the ultimatum game (UG) have recently been discussed in light of models of reciprocity and fairness-related behavior. It has been suggested that behavior following norm-oriented, internalized expectations of reciprocity requires overcoming economic self-interest. In this study we investigated both, behavioral and peripheral-physiological indicators of inhibitory capacity related to neuronal networks that are likely to be involved in the behavioral response to unfair offers. Both heart-rate variability as an index of inhibitory capacity, and performance in a motor response inhibition task predicted rejection of unfair offers in an ultimatum game, suggesting an important role of inhibitory processes in overcoming economic temptations and regulating behavior conforming to social norms of reciprocity and fairness. The role of parasympathetic activity as a physiological trait-marker predicting inter-individual differences in the rejection of unfair offers is discussed.